Growth of upland rice in different populations and supplemental irrigation - Baêta dos Santos, Alberto; Dias Costa, José (Pesquisa Agropecuaria Brasileira, 1997)
Four experiments were carried out on cerrado soil in order to study the effects of three row spacings (0.3; 0.4 and 0.5 m) and three seed densities (50, 100, and 150 seed.m-2) on growth of two rice (Oryza sativa L.) varieties with and without sprinkler supplemental irrigation. Two experiments were carried out with the Araguaia variety (medium growth duration) and two with the Guarani variety (short growth duration). The growth rates of leaf area index (LAI) and total dry matter (DM) were adjusted to quadratic and exponential regressions. Irrigation increased DM, LAI, crop growth rate (CGR) and leaf area duration (LAD) in both varieties. The Guarani variety had higher DM, showing higher values of CGR, and reached fastly the maximum LAI, with high capacity to exploit the available surface than the variety Araguaia. The increasing of the spacing showed a decrease in LAI, LAD, and CGR in both varieties. LAI and DM per tiller were positively correlated with the grain yield with higher coefficient correlation in 30 and 10 day before flowering in the varieties Araguaia and Guarani respectively, without irrigation and in the final flowering under supplemental irrigation.